Pengaruh Media Smart Card Terhadap Kemampuan Menyusun Kalimat Dasar Bahasa Indonesia (SPOK) Pada Siswa Disabilitas Rungu Kelas IV Di Sdlb Ypac Bcd Jember - Balboa, Agam; Sukmawati , Bhenita; Prystiananta, Nostalgianti Citra (Universitas Hamzanwadi, 2025)
This study aims to explore the extent to which smart card media can support students with hearing impairments in constructing basic Indonesian sentences based on the Subject, Predicate, Object, and Adverbial (SPOK) structure. The primary focus of this research is to examine the impact of using smart card media on the sentence-building skills of students with hearing disabilities. In general, the study seeks to assess the effectiveness of smart card media in facilitating the learning process of basic sentence construction in Indonesian. More specifically, it aims to assist hearing-impaired students in improving their ability to formulate sentences that follow the SPOK structure.The research adopts a Single Subject Research (SSR) approach, which emphasizes detailed observation of a single individual to identify changes resulting from a specific intervention. The study employs an A-B design, using the frequency of the target skill’s appearance as the unit of measurement. Through this investigation, it is expected that new insights will emerge regarding the potential of smart card media in fostering the development of basic sentence construction skills in line with the SPOK pattern. The anticipated outcome is empirical data that demonstrate the media's effectiveness in the learning process and provide a foundation for designing similar educational strategies in the future.